Evaluation of macular microvasculature in basic intermittent exotropia by optical coherence tomography angiography - Chun-Wen Chen; Jing-Yan Yao (Scientific Reports)
Abstract To explore the difference in foveal microvascular features using optical coherence tomography angiography (OCTA) between basic intermittent exotropia (IXT) and age-matched controls to observe IXT progression by fundus examination. Recruitment to the analyse and data analysis occurred from August 2021 to June 2022. Participants aged 7 to 17 years old including IXT and age-matched controls were divided into two groups, IXT and control group from clinic in the First Affiliated Hospital of Soochow University (n = 74). All participants undergo basic opthalmologic examination and OCTA scan. The parameters including various regions of retinal thickness (RT), the macular density of deep capillary plexus (DCP), superficial capillary plexus (SCP), and foveal avascular zone (FAZ). A total of 35 (70 eyes) IXTs, and 39 (39 eyes) controls were enrolled. Compared with controls, macular and inferior RT was thicker in IXT groups (p > 0.05). IXT patients were divided into moderate (20∆ < PD ≤ 40∆) and large (40∆ < PD ≤ 60∆) angles of deviation groups. The SCP and DCP were not significantly thinner in deviated eyes than those in dominant eyes and controls.(p > 0.05) No difference was found in various angles of deviation groups in any OCTA parameters. Compared with controls, no alterations in microvascular features were investigated in basic IXT using OCTA. The angles of deviation may not promote macular perfusion. The specific role of macular density in the diagnosis, management, and pathogenesis of IXT is unclear, further analyses may yield to be performed.